A Novel Fault Detection and Location Approach for DC Zonal Shipboard Microgrid Based on High-Frequency Impedance Estimation With IEC 61850 Communication Protocol - Asmaa M. Aboelezz; Magdi M. El-Saadawi; Abdelfattah A. Eladl; Vladimir Bures; Bishoy E. Sedhom (IEEE Access, 2024)
This paper introduces an innovative adaptive scheme for detecting and locating faults in DC-zonal shipboard microgrids (SBMGs). This scheme relies on the estimation of high-frequency impedance. The proposed scheme is implemented in an intelligent electronic device (IED) in which the Fast Fourier Transform is applied to obtain the high-frequency components of the current and voltage at each node. Then, these components are exchanged between the two IEDs that protect the same line by using IEC 61850 GOOSE-based communication system. The estimated high-frequency impedance of the line is calculated and compared to the prescribed settings to detect and locate the fault. After fault detection and localization, communication signals are exchanged between the two IEDs positioned at each end of the line. This exchange precedes the transmission of tripping signals to the relevant circuit breakers for the accurate isolation of the faulty line. The proposed protection scheme is tested through MATLAB/Simulink Ⓡ environment. The scheme can detect and locate the fault under different uncertainty conditions, such as fault impedances, various system configurations, changes in system loads and generations, multi-faults’ existence, contingency conditions, and the presence of noise on the communication signals. The results proved its efficient performance and superiority. The scheme can detect and locate the faults quickly and accurately within 0.125 ms.